DEVELOPMENT OF PHYSICS LEARNING DEVICE WITH BATAK CULTURE BASED COOPERATIVE LEARNING MODELS - Rika Sari Indah Harahap; Derlina Nst; Zainal Abidin (Jurnal Pendidikan Fisika, 2019)
This study aims to describe the validity, practicality and effectiveness through Batak culture based cooperative learning models and to know the improvement of generic science skills and student’s teamwork by applying learning tools through Batak culture based cooperative learning models. This research is a Research and Development (R & D) using the 4-D model that includes define, design, develop, and disseminate.  This research was conducted at the school of SMA Negeri 1 Tambangan with a population of 21 students in class X MIA I. Instruments and techniques of data collection using learning device validation sheets, namely validation sheets of lesson plan (RPP), validation sheets for student worksheets (LKS), validation sheets for generic science skills instruments and student’s teamwork, sheets of learning practicality assessment, learning effectiveness sheets, learning activity instruments, instruments generic science skills and student’s teamwork questionnaires. Improved generic science skills and  student’s teamwork using analysis with N-gain test. The results showed that the learning materials through Batak culture based cooperative learning models had met the criteria of valid, practical and effective. Students generic science skills increase to the medium category and there is an increase in student’s teamwork with the medium category